FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KEJADIAN ASAM URAT (GOUT) PADA USIA ≥ 45 TAHUN DI DESA UJUNG SERDANG KECAMATAN TANJUNG MORAWA TAHUN 2016 - irma yani manullang; Rasmaliah .; Jemadi . (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2016)
ABSTRACT Gout is degenerative disease and kind of rheumatic disease who many finded of erderly pose. The record of gout in Tanjung Morawa’s public health center are combined with disease of the muscular system and connective tissue (bone diseases, including rheumatoid arthritis). The gout is sixth rank of ten the disease greatest in Tanjung Morawa’s public health. This study was aimed to analyze the factor related to gout in work region of Tanjung Morawa’s Public health center in 2016 year. This research is observational analytic using cross sectional design. The population in this study were all citizens whose ages are ≥45 years old in Ujung Serdang village. Samples were taken by using multi stage random sampling with a number of samples which are 100 people. Primary data were obtained by doing interviews with questionaires and food frequency questionaires and getting blood uric acid by the nurse. Secondary data were getting from Tanjung Morawa public health center and master of Ujung Serdang village office. Data analysis was commited by using to the univariate, bivariate, and multivariate analysis with computer. The results of bivariate analysis revealed that the variables were related to gout were family history (p=0,015) and comsumption of purine (p= 0,001). The population ages are >55 tahun have high risk to contribute of gout. Multivariate analysis by using Bacward Selection revealed that the most dominant variabel which was related to gout was comsumption of purine (p= 0,001; OR= 4,139; CI 95%= 1,7269,928). It’s expected that the community could make healthy lifestyle and to the risk population must diet the comsumption of food consisting of purine that can increase levels of gout on blood and checkup to servicing of health in periodic . Keyword : Gout, Hiperurisemia, Population ages are ≥45 years old